Effects of (Ba₀.₆Sr₀.₄)TiO₃ ceramic and ZnO-TeO₂ glass doping ondielectric properties of CaCu₃Ti₄O₁₂ ceramics / Norezan Ibrahim - Ibrahim, Norezan (2014)
In this study, the separate effects of (Ba₀.₆Sr₀.₄)TiO₃ (BST) ceramics and ZnO-TeO₂ glass additions on dielectric properties of CaCu₃Ti₄O₁₂ (CCTO) ceramics were investigated and prepared from high purity oxide powders by the conventional solid state synthesis method . For the first series, (1-x)CCTO- (x)BST (x=0,0.05, 0.1, and 0.2) composite, X-ray diffraction (XRD) analysis showed the existence of BST as a secondary phase alongside CCTO. Scanning electron microscopy (SEM) showed a slight decrease in grain size of doped CCTO samples. Addition of BST into CCTO caused the dielectric constant to slightly decrease but improved stability with frequency compared to the undoped sample. The decrease in dielectric constant of doped CCTO samples was suggested to be partly due to the decrease in average grain size and increase in porosity with BST addition. The dielectric loss (tan ᵹ) of CCTO reduced by the BST addition and probably due to the increase of grains boundary resistivity. The activation energy of grains boundary (Egb) showed higher values as compared to the activation energy of grains (Eg) for all samples and conforms to the internal barrier layer capacitor (IBLC) model. For the second series (1-x)CCT0-(x)( ZnO-TeO₂) (x=0,0.01, 0.03, and 0.05) glass composite, XRay diffraction investigation showed single phased CCTO for all samples without presence of any crystalline phase related to ZnO-TeO₂. Scanning electron microscope (SEM) showed the grain size of CCTO ceramics increased with increasing addition of ZnO-TeO₂ glass additive. The addition of ZnO-TeO₂ glass improved the dielectric constant of CCTO for entire frequencies probably due to the increase of grain size ofCCTO ceramics. In addition, it was found that the dielectric loss of CCTO reduced by the ZnO-TeO₂ glass addition and it was suggested to be due to the increase of grain boundary resistivity. The resistance of grains boundary (Rgb) showed higher values as compared tothe resistance of grains (Rg) for all samples and the large difference between theresistances also conforms to the IBLC model.